Economic linkages amond irrigation sources: A study of the beneficial role of canal seepage - Dhawan, B. D.; Satya Sai, K. J. S. (International Food Policy Research Institute, 1990)
The new biochemical technology of crop farming has had uneven success in India. In view of the continental diversity of Indian agriculture this is hardly surprising. ts limited success has been linked inter alia with farmers' acces:; to dependable sources of irrigation, notably individually owned tubewells and pumpsets, which are ideally suited for meeting the exa:ting water requirements of high-yield variety (HYV) wheat and padcy. Groundwater irrigation has been identified as the key to agricu tural transformation, and a groundwater development lobby has emerged in the country.